The material deformation modes of monocrystalline gallium antimonide (GaSb) under nano-scratching - Wang, Ziguang; Yan, Feng; Zhang, Yu; Ma, Jiaheng; Zhou, Ping; Kang, Chengwei; Sha, Zhihua; Zhang, Shengfang (Frontiers in Materials, 2023)
Gallium antimonide (GaSb) is a new type of semiconductor material that is getting popular in optical and electronics applications. The ultra-precision grinding is one of the most important machining methods to obtain a high-quality GaSb substrate. The deformation characteristics of GaSb are in-vestigated by employing nano-scratch tests to understand the material removal mechanism during ultra-precision grinding. The nano-scratches are obtained by a cube-corner tip under the two linear normal load conditions (0-30 mN and 0-60 mN). The normal force /scratch distance-penetration depth curves and the characteristics of chips and cracks are analyzed to understand the transition mechanism of ductile to brittle removal. In addition, the maximum principal stress near the bottom of the scratch is calculated to analyze the deformation behavior. Following the conclusion of the deformation mode transitions, the results revealed the deformation behavior of three zones of de-formation, and the corresponding critical value of normal force is determined as 13±1 mN and 18±1 mN, respectively.